2020
DOI: 10.15587/1729-4061.2020.209778
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of steam generation performance on conical cavity receiver by different geometric concentration ratios for fresnel lens solar concentrator

Abstract: air in an isolated chamber, for example, in a food drying system. Third, conduction is the heat transfer due to sunlight absorbed by the collector/absorber/receiver, which will then be delivered to the object to be heated (water heater). The development of the combination of these three combinations of heat transfer was carried out by many researchers for various applications of solar thermal technology. The type of solar collector used today still uses conventional types from both the material and the type. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These parameters include location, operating temperature, radiation level, radiation spectrum, wind speed, angle of incidence and several other factors. This causes the actual efficiency to differ from the efficiency measured in the manufacturer's manual [11]. Several factors that affect the performance parameters of PV Modules include surface area, solar radiation, ambient temperature, weather, and other factors.…”
Section: Theory Of Pv Module Performancementioning
confidence: 99%
“…These parameters include location, operating temperature, radiation level, radiation spectrum, wind speed, angle of incidence and several other factors. This causes the actual efficiency to differ from the efficiency measured in the manufacturer's manual [11]. Several factors that affect the performance parameters of PV Modules include surface area, solar radiation, ambient temperature, weather, and other factors.…”
Section: Theory Of Pv Module Performancementioning
confidence: 99%
“…However, according to the author [17], nowadays the application of solar thermal energy concentrators is still dominated by the reflective method of mirrors in the form of a parabolic trough collector, linear Fresnel reflector (LFR), parabolic dish, and central receiver. One of the weaknesses of this model is that the material is heavy, so it needs a sturdy framework, so it is not economical.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…A study conducted by Asrori and Susilo [18] using a Fresnel lens to heat 2 liters of water found a temperature of around 70 °C, but they did not report the type of absorber used. Furthermore, the Fresnel lens application also has the potential to be used for steam generation [19] and solar cookers [20]. Moreover, Rashid et al [21] reported in their review study that Fresnel lenses have broad applications such as photovoltaics, solar stills, solar thermal collectors, solar sterilization, solar cookers, and solar-pumped lasers.…”
Section: Introductionmentioning
confidence: 99%